2021
DOI: 10.3389/fcell.2021.767510
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Reprogramming and Cell Adhesion in Acute Leukemia Adaptation to the CNS Niche

Abstract: Involvement of the Central Nervous System (CNS) in acute leukemia confers poor prognosis and lower overall survival. Existing CNS-directed therapies are associated with a significant risk of short- or long-term toxicities. Leukemic cells can metabolically adapt and survive in the microenvironment of the CNS. The supporting role of the CNS microenvironment in leukemia progression and dissemination has not received sufficient attention. Understanding the mechanism by which leukemic cells survive in the nutrient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 147 publications
0
8
0
Order By: Relevance
“…S4G), suggesting their potential as a biomarker for brain in ltration in B-ALL. Previous studies have been extensively reviewed the impact of speci c genetic lesions [44], CNS niche [45], chemokines and cytokines [46,47], growth factors [48], metabolic reprogramming and cell adhesion [49] in driving leukemic cells to the CNS. Although ACSM3 involving in the fatty acid metabolism [50] and HRK playing a pro-apoptotic role by interacting with BCL2 [51] have been reported, the functions on CNS leukemia remains unknown and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…S4G), suggesting their potential as a biomarker for brain in ltration in B-ALL. Previous studies have been extensively reviewed the impact of speci c genetic lesions [44], CNS niche [45], chemokines and cytokines [46,47], growth factors [48], metabolic reprogramming and cell adhesion [49] in driving leukemic cells to the CNS. Although ACSM3 involving in the fatty acid metabolism [50] and HRK playing a pro-apoptotic role by interacting with BCL2 [51] have been reported, the functions on CNS leukemia remains unknown and requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors devote a great part of their energy consumption to growth; therefore, a downregulation of metabolic demand and tissue acidification define the hypoxic parts of a tumor, which is a physiological result of rapid growth and insufficient circulation [ 67 ]. Stimulated by hypoxia, the hypoxia-inducible factor (HIF) can activate transcription factors that target genes involved in tumor microenvironment remodeling, tumorigenesis, and metastasis processes such as metabolism, growth, EMT, angiogenesis, immune evasion, and resistance [ 30 , 53 , 67 , 90 , 93 , 94 , 95 ].…”
Section: Involvement Of Itga6 In Cancer Metastasismentioning
confidence: 99%
“…Otto Warburg was the first to describe tumor cells’ abnormal metabolic function [ 96 , 97 ]. Recent research has found that cancer cell adhesion, which is a key regulator of leukemia growth and chemoresistance, may either induce or be induced by metabolic reprogramming-related cell signaling pathways [ 95 ]. ROS may activate numerous oncogenic pathways (e.g., PI3K/AKT, NF-κB, and p38/MAPK) by stabilizing HIF1 [ 98 ].…”
Section: Involvement Of Itga6 In Cancer Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…adaption to the CNS microenvironment and contact-induced quiescence. Accumulating evidence supports that the low oxygen and nutrient availability in the CSF induce metabolic adaptations in the leukemic cells that promote their survival in the CNS microenvironment [110]. Several studies have shown that hypoxia-gene expression signatures are upregulated in leukemic cells located in the CNS, and that treatment with the anti-VEGF antibody bevacizumab significantly reduced CNS leukemia in ALL xenograft models [85,111].…”
Section: Novel Drugs That Target Cell Survival Mechanismsmentioning
confidence: 99%